Exploration Of Students’ Argumentation Skill Assisted Format Representation In Solving Electrical Concept - Rikardus Feribertus Nikat (JURNAL PENDIDIKAN SAINS (JPS), 2021)
The argumentation skill is one of the supporting abilities in determining the quality of thinking in the era of the 4.0 revolution. The development of argumentation skills is important to be implemented in solving physics problems, especially in exploring how they solve problems and understand concepts so that misconceptions do not occur. This study aims to determine the improvement of students' argumentation skills in solving electrical concept problems before and after the intervention. This type of research uses a mixed method model research method with an embedded experimental design. The research subjects consisted of 32 students of the Department of Physics Education at Musamus University who had or are currently taking the magnetic electricity course. The results showed that students' argumentation skills improved along with the help of worksheets assisted with representation formats during lectures